Masyarakat Indonesia Kontemporer dalam Pusaran Komunikasi - Burhan Bungin (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
There are 3 points to discuss the Indonesian contemporary society who lives in reformation order. First is urban society with liberalism perspectives, open and information technology in their hand. Second is structuralist society, who lives and willingness in patron – client/ leadership traits. Third is marginal society with less access to education, health system and powerless. In the development of reformation order, with new perspectives and interpretation, there are some changing in our society, rapidly moved. What implication, also with communication perspectives? Also what is going to happen next , are parts of the discussion in this article.